MORBIDITY PROFILE OF THE UNDER FIVE CHILDREN IN URBAN SLUMS OF ETAWAH DISTRICT. - Srivastava, Dhiraj Kumar; Tripathi, Dhirendra; Gour, Neeraj; Jain, Pankaj Kumar; Singh, C M; Srivastava, Alok Kumar; Kumar, Sandip; Rani, Vidya (Indian Journal of Community Health, 2012)
Background: Children are the backbone of any country and their health is a prime concern of the country. The under five years is an important age group as the morbidity profile of this age group will have a far reaching consequences on the overall development of the country. Objectives: · To find out the morbidity profile of under five children in the urban slums · To find out the co-rrelates of the study. Material and Methods: The present study was a Cross Sectional Study carried out for a period of six months from January 2011 to June 2011. The examination was carried out using a pre designed proforma. Information regarding the immunization and history of any acute illness in last six months was gathered by interview followed by Physical Examination which included anthropometric measurement, that is, weight, height/length, mid arm circumference, head circumference and chest circumference. Result: In the present study, only 33.94 % children were completely immunized. Diarrhea and Upper Respiratory Tract Infections were the most common morbidities reported in the age group of 1-5 years. There were no statistically significant differences in the anthropometric profile of the male and female child. 31.7% of male and 23.2% of female child were underweight as compared to the normal standard weight as per their age. 17.9 % of male and 20.1% female were stunted. Conclusion: The present study hereby concludes that the Diarrheal Diseases and Upper Respiratory tract Infection are the majorities common among the children of under five years in slum dwellers.